Intelligent Peer-To-Peer Banking Framework: Advancing The Frontiers of Agent Banking For Financial Inclusion In Nigeria Via Smartphones - Arnold Adimabua Ojugo; Oghenevwede Debby Otakore (Yayasan Ahmar Cendekia Indonesia, 2020)
The advent of the retail point of sale (POS) system as a critical component of the traditional retail infrastructure seeks to advance client payment-ease for goods and services rendered by vendors as well as the effective collection of funds by the vendor. It also aids the vendor to collect in advance monies that the client may wish to spend later on goods and services. Thus, the POS has since become a necessity in modern retail stores as its increased usage has seen a transformation from a single machine to a cloud and smart platforms. Our study seeks to model a conceptual framework for decentralized POS as adapted to smartphones. This will enhance cashless transaction irrespective of a customer’s location globally and locally. Built around the block-chain technology, it seeks to minimize challenge(s) of time, installation requirements incurred with the adoption of automatic teller machine (ATM), location and citing of agent-banking in a rural area with low tele- and tech-penetration.